2019
DOI: 10.18203/2319-2003.ijbcp20195283
|View full text |Cite
|
Sign up to set email alerts
|

A study on knowledge, awareness and preventive practice about tuberculosis among medical students in Udaipur, India

Abstract: Background: Tuberculosis (TB) is a highly lethal infectious disease causing huge health burden worldwide, commonly involving the respiratory system. Medical students should also be empowered to impart awareness and reduce stigma related to TB. The objective of this study was to evaluate whether educational intervention would affect the level of TB awareness, knowledge, attitude and preventive practice of TB among medical students.Methods: The present study was carried out among the second year medical college … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(36 reference statements)
1
1
0
1
Order By: Relevance
“…It also reported that healthcare students in Rome, Brazil, Nigeria, and China had poor knowledge about the disease ( 27 ). Similar findings were reported in a study carried out in India, where healthcare students’ knowledge was assessed through a pre-test questionnaire, and their average score was 48.59 (± 20.44) ( 28 ). In Jordan, students reported knowledge gaps in TB treatment and transmission with a median score of 27 out of 51 ( 29 ).…”
Section: Discussionsupporting
confidence: 86%
“…It also reported that healthcare students in Rome, Brazil, Nigeria, and China had poor knowledge about the disease ( 27 ). Similar findings were reported in a study carried out in India, where healthcare students’ knowledge was assessed through a pre-test questionnaire, and their average score was 48.59 (± 20.44) ( 28 ). In Jordan, students reported knowledge gaps in TB treatment and transmission with a median score of 27 out of 51 ( 29 ).…”
Section: Discussionsupporting
confidence: 86%
“…Se observa que la región con mayor carga de la enfermedad: Eje Cafetero en la cual los estudiantes rotaciones clínicas en los diferentes centros de atención médica podrían tener mayor oportunidad de atender pacientes con relación con los hallazgos evidenciados en la literatura, el tiempo y el número de pacientes están relacionados al nivel de conocimientos en TB de los estudiantes de último año de medicina (17,18) .…”
Section: Discussionunclassified
“…[ 23 ] Surprising results were observed in Samal J study, which stated that 97% of the slum dwellers of Chhattisgarh were aware of TB symptoms and in another study conducted by More BD et al among second year medical graduates, only 60.6% were aware of symptoms. [ 14 24 ] In the study conducted by Nigatu DT et al in the societies of Holeta town, 34.2% of the subjects opted cough, 33.6% opted weight loss, and 17.5% opted persistent fever and in another study conducted by Datico DG et al among general population of Ethopia, 85.5% identified cough and 17.1% opted fever as symptoms of TB. [ 5 22 ]…”
Section: Discussionmentioning
confidence: 99%